Validación preliminar del modelo de liderazgo espiritual de Fry en trabajadores colombianos y ecuatorianos (2017)
The aim of this study was to examine the validity of the Spiritual Leadership model proposed by Fry (2003). Spiritual Leadership Questionnaire [SLT] (Fry & Matherly, 2006) was applied to 279 workers from Colombia and Ecuador. The two samples were equivalent by sex, age, education level and work experience. According to the results, all dimensions of the questionnaire showed to be highly consistent (alpha above .85) except Commitment dimension. Likewise, it found that just one of 35 items that composed the scale shows low item-scale correlation. In the most of the cases, the relationships between variables as well as the adjustment index of the model were lower than reported by Fry previously, which limited the construct validity. External evidences of validity of the model, demonstrated that the work experience and level of charge were significant for Spiritual Leadership dimensions. These findings were related to the psychometrics requirement of the scale and regarding of measured construct with organizational behavior. Finally, it is point out some research limitations and provide some suggestions for future studies.